Efek Nefroprotektif Ekstrak Etanol Buah Jambu Biji Merah (Psidium guajava Linn) terhadap Kerusakan Histologis Ginjal Mencit yang Diinduksi Asetaminofen - Prisca Priscilla; . Suyatmi; Yulia Sari (Nexus Kedokteran Translasional, 2013)
Background: Red guava fruit (Psidium guajava Linn) contains various of antioxidants such as vitamins A, C, E, minerals Fe, Zn, Se, flavonoids, and lycopene, which they were thought to have nephroprotective effect. The objective of this research was to evaluate the preventive effect of red guava fruit ethanolic extract on tubular renal damage induced by acetaminophen on mice. Methods: Samples were twenty eight male mice, Swiss webster strain, 2-3 months old age and + 20 gram of each weight. Sample divided into 4 groups, each group consists of seven mice. The negative (KK(-)) and positive control group (KK(+)) mice were given aquadest for 14 days. The other group of mice were given red guava fruit ethanolic extract with the dose of 35 mg/20 g body weight of mice (KP1) and the last group of mice were given red guava fruit ethanolic extract with the dose of 70 mg/20 g body weight (KP2) for 14 days. Acetaminophen was given to groups of KK(+), KP1, and KP2. The 15th day, mice were sacrificed and histological preparation were made to evaluate histological damage on rens. Renal histological features were assessed by counting the number of tubular epithelial undergoing pyknosis, karyorrhexis, and karyolysis. Data were analyzed using the One-Way ANOVA test (? = 0.05) and then were continued with Post Hoc Multiple Comparisons (LSD) test (? = 0.05). Results: The mean renal histological damage score was significantly higher on group KK(+)= 40.50+1.991, while the group of KK(-)= 8.93+1.720 as the less. The group of KP2 had fewer numbers of renal histological damage (17.96+1.621) compared to the KP1 group (25.36+1.929). The results of One-Way ANOVA and LSD test showed that there was significant difference between the four groups (p = 0.000). Conclusions: The ethanolic extract of red guava fruit showed nephroprotective effect to the renal histological damage of mice which was induced by acetaminophen. Red guava fruit ethanolic extract with the dose of 70 mg/20 g body weight of mice showed a higher nephroprotective effect than the dose of 35 mg/20 g body weight of mice. Keywords: ethanolic extract, red guava, acetaminophen, renal histological, mice.